Insulin-like growth factor system in neuroblastoma tumorigenesis and apoptosis: potential diagnostic and therapeutic perspectives - Zumkeller, Walter; Schwab, Manfred (Hormone and metabolic research, 1999)
Apoptosis is a cell death program which is modulated by a variety of factors including growth factors, signal transduction molecules and inducers of gene expression or DNA replication. Of particular interest is Type I insulin-like growth factor receptor which contains a tyrosine kinase domain linked to the ras-raf-MAPK cascade. This receptor has antiapoptotic effects in a number of in vivo and in vitro models, thus making IGF-I-R a potential target for gene therapy. Particularly the growth of neuroblastoma depends on IGFs which exert their effect through the Type I IGF receptor. This review highlights the role of the IGF-system in neuroblastoma and points at possible modulators with the aim of inducing differentiation or apoptosis of tumor cells.
Elektronische Reproduktion der Druckausgabe
Gesehen am 15.02.2019